Analysis of the Variability of Axial Bearing Capacity of Piles in Cohesionless Soil in the Development of Meyerhof Formula - Krisnanto, Sugeng; Kabila, Merizka Putri; Amiruddin, Moch. Darril; Wijayadi, Septian; Adryan, Feby; Ikrimah, Ikrimah (Jurnal Teknik Sipil, 2024)
Abstrak Rumus daya dukung pondasi tiang dari Meyerhof (1976) banyak digunakan di Indonesia. Sangat penting untuk mengkuantifikasi variabilitas dalam perancangan. Ini juga berarti sangat penting untuk mengkuantifikasi variabilitas daya dukung aksial tiang terhadap nilai N-SPT dalam rumus yang banyang digunakan seperti rumus Meyerhof (1976). Analisis untuk mengkuantifikasi variabilitas yang terkandung dalam rumus daya dukung aksial Meyerhof (1976) dilakukan dalam makalah ini. Dalam analisis, digunakan data dalam publikasi Meyerhof (1976). Hubungan antara probabilitas kegagalan dan faktor keamanan untuk rumus daya dukung formula dikuantifikasi. Dari studi ini didapatkan bahwa faktor keamanan untuk rumus daya dukung aksial ujung tiang adalah sebesar 1,54, 2,17, dan 1,35 untuk pondasi tiang pancang pada tanah pasir, pondasi tiang pancang pada lanau, dan pondasi tiang bor. Juga didapatkan bahwa faktor keamanan untuk rumus daya dukung aksial selimut tiang adalah sebesar 1,54 untuk tiang pancang di tanah pasir dan lanau, dan 1,14 untuk tiang bor. Kata-kata Kunci: Daya dukung aksial tiang, Rumus Meyerhof (1976), Probabilitas kegagalan, Faktor keamanan, Variabilitas daya dukung aksial tiang. Abstract Meyerhof (1976) formula for calculation of pile axial bearing capacity is quite familiar in Indonesia. It is essential to quantify the variability of soil in a design. This also means, it is essential to quantify the variability of axial pile bearing capacity versus N-SPT inherited in a commonly used formula like Meyerhof (1976) formula. An analysis to quantify the variability inherited in Meyerhof (1976) formula for calculation of pile axial bearing capacity was performed. The data in the publication of Meyerhof (1976) are used in the analysis. The relation between the probability of failure for pile and the factor of safety in terms of the axial bearing capacity formula was quantified. It was found that the factors of safety for formula of unit pile tip bearing capacity are 1.54, 2.17, and 1.35 for driven pile in sand, driven pile in silt, and bored pile in sand, respectively. Also, it was found that the factors of safety for formula of unit pile shaft bearing capacity are 1.54 and 1.14 for driven pile in sand and silt and bored pile in sand, respectively. Keywords: Axial pile bearing capacity, Meyerhof (1976) formula, Probability of failure, Factor of Safety, Variability of axial pile bearing capacity.